Outbreak of equine coronavirus disease in adult horses, Switzerland 2021. Issue 4 (22nd March 2022) - Hierweger, Melanie M.; Remy‐Wohlfender, Franziska; Franzen, Jan; Koch, Michel C.; Blau, Désirée; Schoster, Angelika; Nicholson, Pamela; Gerber, Vinzenz; Gurtner, Corinne; Fouché, Nathalie; Unger, Lucia; Seuberlich, Torsten
Abstract: Coronaviruses are causing severe respiratory and enteric diseases in humans and animals. Here, we report an outbreak of equine coronavirus disease in adult horses, detected by a voluntary syndromic surveillance scheme for equine diseases in Switzerland. This scheme allowed a rapid concerted action to diagnose and contain the disease.